Perbuatan sebagai Masalah Filsafat dan Implikasinya bagi Kemungkinan Wahyu Adikodrati: Perspektif Filsafat Agama Maurice Blondel - Binsasi, Norbertus Antoin (Medan Resource Center, 2024)
For the first time “action” was raised by Maurice Blondel, a contemporary French philosopher, as a philosophical problem. With actions carried out with “knowing” and “wanting” (actus humanus), so desired actions, the human will can move from limited reality to the Divine as unlimited reality. For Blondel, two types of will are used, volonte voulante (the willing will) and volonte voulue (the willed will). Volonte voulue is a type of human action whose object is empirical goods, because it is always possible to achieve them. Meanwhile volonte volulante is a type of action whose object concerns metaempirical reality and is therefore difficult and even impossible to achieve by the effort of the human will. This object can only be achieved by humans thanks to the actions of the Divine Himself, namely through God's own Revelation which comes to humans. Blondel's contribution to contemporary religious philosophy lies here, namely that he can rationally account for the faith of religious people that believers are made possible by the natural capacity in humans, namely the dynamism of the will to lead him to the possibility of supernatural revelation. However, philosophy here only provides a “possibility” not “certainty”. Meanwhile, “certainty” regarding the existence of special revelation (divine revelation based on the Holy Scriptures) remains a matter of theology as a matter of certainty of faith.